THE POTENTIAL IMPACT OF INADEQUATE TRANSLATION: MEANING ALTERATION AND DECREASED COMPREHENSION IN THE INDONESIAN TRANSLATION OF LAMB TO THE SLAUGHTER - Mubarokah, Indhana Alfania Fadhilatal; Subiyanto, Arif (Jurnal Pembelajaran Sastra, 2024)
Translation is a complex art that plays a pivotal role in bridging cultures and facilitating the exchange of knowledge across languages. However, when translation falls short of exacting standards, it can alter meanings and affect reader comprehension. The author intended to suggest an alternative translation to the current online Indonesian translation of Roald Dahl’s short story Lamb to the Slaughter, and compare the results in the discussions. By analysing changes in word and phrase choices, this project reveals that inadequate translation can significantly alter the meaning of the story. This study analyzes the differences between two translated texts using Eugene Nida's equivalence theory. The project aims to understand how the principles of formal and dynamic equivalence are applied in the translation of Lamb to the Slaughter. The methodology employed is a comparative analysis of the two texts, focusing on language structure and fidelity to the original meaning. The findings indicate that translations using dynamic equivalence are more effective in conveying contextual meaning, while formal equivalence better preserves the original language structure.